Determinants of SMEs performance: The role of knowledge management, market orientation, and product innovation - Setiyono, Wisnu Panggah; Iqbal, Mohammad; Alfisyahr, Rizal; Pebrianggara, Alshaf; Shofyan, Mukhammad (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2022)
The role of knowledge management (KM) in the existence of Small Medium Enterprises (SME’s) has been an important aspect of entrepreneurship. However, to perform an SME may not merely rely on its knowledge but also on other aspects such as market orientation and product innovation. This study aims to contribute to the entrepreneurship literature in the context of emerging economies. This study can be classified as quantitative research by nature as the use of a survey to gather respondent data. About 211 samples of SMEs of the furniture cluster in East Java were obtained in this study. Thus, understanding that the focus on market orientation and innovation in SMEs has not fruitfully been exposed and explored enough in the context of emerging economies such as Indonesia. The result of this study indicated that KM is not a direct predictor of SME performance. This is an indication that the supremacy creation of SME performance could not depend heavily on KM but rather, other driving forces such as market orientation (MO) and product innovation (INNOV) are much more powerful drivers in crafting SME performances.